The Ideas of E.Durkheim and M.Foucault in a Synthetic Penal theory of D.Garland - Gavėnaitė, Aušra (Sociologija. Mintis ir veiksmas, 2008)
The article presents American penologist’s David Garland’s social theory of punishment. The main aim is to show the background of his ideas and the theoretical foundations of his studies. Article shows what ideas of E. Durkheim and M. Foucault have been introduced into penal theory of American penologist. Article describes and highlights these aspects: E. Durkheim regards punishment as an outcome of collective consciousness and gives tools for its sociological analysis; theoretical approach of M. Foucault shows punishment as the tool of power in disciplinary society of the XXth century. These ideas on punishment were neatly synthesized and introduced into D. Garland’s approach to punishment. Article also analyses the concept of “culture of control” that is suggested by D. Garland to name the culture of crime prevention field in the second half of the XXth century. This analysis makes a conclusion that punishment is not the tool of crime control in a narrow penal sense but has wider social and cultural background.